Synthesis of Geometry Proof Problems - Alvin, Chris; Gulwani, Sumit; Majumdar, Rupak; Mukhopadhyay, Supratik (AAAI'14 Proceedings of the Twenty-Eighth AAAI Conference on Artificial Intelligence, 2014)
This paper presents a semi-automated methodology for generating geometric proof problems of the kind found in a high-school curriculum. We formalize the notion of a geometry proof problem and describe an algorithm for generating such problems over a user-provided figure. Our experimental results indicate that our problem generation algorithm can effectively generate proof problems in elementary geometry. On a corpus of 110 figures taken from popular geometry textbooks, our system generated an average of about 443 problems per figure in an average time of 4.7 seconds per figure.